Personalized Care with DPP4i/SGLT2i Strategy as Initial-Line in the Management of Type 2 Diabetes Mellitus with Cardiovascular Risk: DELPHI Statement - Sahay, Rakesh Kumar; Baruah, Manash; Keswani, Prakash; Phatak, Sanjeev; Chawla, Manoj; Sooragonda, Basavaraj G; Kakkad, Ashutosh; Chouksey, Narendra; Korukonda, Krishnaprasad (Cardiology and Cardiovascular Medicine, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a highly prevalent metabolic disorder in Asian-Indians owning to distinct phenotypic traits including impaired Insulin sensitivity and resistance, necessitating personalized management to avoid progression towards cardiometabolicbased chronic disease (CMBCD) or complications. Objective: To develop Consensus on the Indian perspective for management of T2DM with high cardiovascular (CV) risk by a National Expert panel. Methods: A steering committee (n=6) developed DELPHI statements using a Knowledge, Attitude, and Perception questionnaire while analyzing the literature review and responses from a National panel (n=152) utilizing AHRQ criteria defined evidence strength and quality. A Likert scale assessed panel responses, with ≥70% of Steering committee agreement documented for clinical recommendations as DELPHI statement. Results: National panel (n=152) emphasized need for early add-on strategies for T2DM patients, as half of the patients present with macrovascular complications. Panel agreed on personalizing treatment being crucial, especially for uncontrolled patients, geriatrics, young patients, and those with additional risk factors or microvascular complications. Favourable risk-benefit profile and clinical outcomes with DPP4 inhibitors & SGLT2 inhibitors combination makes it relevant for early use in T2DM cases including those with ASCVD, heart failure, older and obese individuals who are not controlled on metformin. Conclusion: Need for personalized care strategies combining DPP4i and SGLT2i for T2DM patients with risk stratification score for CMBCD development or progression as highlighted by the CGM studies to avoid the risk of Glycemic variability and/or Hypoglycemia.